2017
DOI: 10.1111/jai.13254
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships of four fish species from the Niulan River, China

Abstract: Summary This study provides the length–weight relationships (LWRs) for four fish species [Leptobotia rubrilabris (Dabry de Thiersant, 1872); Opsariichthys bidens Günther, 1873; Xenocypris yunnanensis Nichols, 1925; and Sinogastromyzon sichangensis Chang, 1944] collected from the Niulan River, China. Samples were obtained between April 2008 and June 2011 using various types of fishing gear [drift gill nets (mesh: 5 × 5 cm), hook and electro fishing]. A total of 136 specimens belonging to four fish species were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
1
6
1
Order By: Relevance
“…However, we also can assume that the estimates are representing fairly well the species‐specific LWR as the r 2 values are all slightly above .95. The present study reports the b value of Sinogastromyzon sichangensis as 3.284, which was different from the study area derived from Niulan River ( b as 3.042) (Zhang, Wang, & Liu, ). The reason may be attributed to (a) different fishing gear selectivity compared to our method, and (b) to different habitat environment scenarios, the study season, and individual biological differentiation (Zhu et al., ).…”
Section: Discussioncontrasting
confidence: 94%
“…However, we also can assume that the estimates are representing fairly well the species‐specific LWR as the r 2 values are all slightly above .95. The present study reports the b value of Sinogastromyzon sichangensis as 3.284, which was different from the study area derived from Niulan River ( b as 3.042) (Zhang, Wang, & Liu, ). The reason may be attributed to (a) different fishing gear selectivity compared to our method, and (b) to different habitat environment scenarios, the study season, and individual biological differentiation (Zhu et al., ).…”
Section: Discussioncontrasting
confidence: 94%
“…For a comparison of b values calculated in our study with 95% confidence limits of Bayesian estimation reported in FishBase (Froese & Pauly, ), the fish species were divided into two groups: (a) one specie with b values within the Bayesian's confidence intervals ( T. siluroides ); (b) three species with both values of the intervals ( S. anteroventris , S. lissolabiatus and T. markehenensis ). Differences in the LWR can be attributed to several factors: a number of factors such as environmental (seasonal variation, habitat type, geographic region) and biological (population, gonadal maturity, sex, growth phase, diet, degree of stomach fullness, health and general fish condition) (Xia, Chen, & Xiong, ; Zhang, Wang, & Liu, ; Zhu, Yang, Liu, & Li, ); however, these factors were not considered in the present study. In addition, the narrow sample size and/or the length range of T. markehenensis possibly affected the b values in the study.…”
Section: Discussionmentioning
confidence: 95%
“…For a comparison of b values calculated in our study with 95% confidence limits of Bayesian estimation reported in FishBase (Froese & Pauly, 2017), the fish species were : coefficient of correlation. Xiong, 2016;Zhang, Wang, & Liu, 2017;Zhu, Yang, Liu, & Li, 2015); however, these factors were not considered in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although Hyphessobrycon anisitsi showed a values within the Bayesian's confidence intervals, the value of this parameter seems to be too high for what would be normally acceptable, thus making this an estimate tentative. The high values of a of these species may be the result of a variety of factors such as season, sex, length ranges and stomach fullness (Haimovici & Velasco, ; Zhang, Wang, & Liu, ). Another important factor that must be taken into account is that for small fish species, such as those of this study, some deviations may occur in LWRs due to changes in length and weight caused by shrinkage and/or dehydration because of fixation prior measurement.…”
Section: Discussionmentioning
confidence: 99%